Strain-tuning Bloch- and Néel-type magnetic skyrmions: A phase-field simulation. (1st January 2023) - Dong, Shouzhe; Wang, Jing; Shi, Xiaoming; Liang, Deshan; Jafri, Hasnain Mehdi; Hu, Chengchao; Jin, Ke; Huang, Houbing
Abstract: Strain manipulation of the magnetic domains, such as the stripe domains and skyrmions, has attracted considerable attention because of its potential applications for magnetic logic and memory devices. Here, utilizing phase-field modeling, we demonstrate the deterministic modulation of the orientation and the configuration of the stripe domains and skyrmions by using a uniaxial strain. The reorientation of the stripe domains can be caused by a suitable strain, and the direction of the reorientated domains is determined by the direction of the applied uniaxial strain and the type of domain walls, including Bloch- and Néel- types. Furthermore, by constructing a phase diagram, we discovered that when the uniaxial tensile strain increases, the ferromagnetic islands undergo a continuous phase transition from a skyrmion to multi-domains or a single domain. The competition between magnetic anisotropy energy and stray field energy leads to the continuous phase transition and the formation of domain patterns under the uniaxial tensile strain. Our research provides a theoretical foundation for the development of strain-controlled magnetic domain designs. Graphical abstract: When the magnetic domains have different domain wall types, the uniaxial strain will cause the domain structure to be precisely reconstructed in a certain direction. Image, graphical abstract